The lively chemistry of transatlantic enterprise: RESEARCH: An attempt by Cambridge university and MIT to create a gateway for new industry in Europe has experienced a clash of cultures. This could explain it's early success, says Jim Kelly: London edition - Kelly, Jim (The Financial times (London ed.), 2001)
It is not difficult to see why Mr [Gordon Brown], after visiting MIT's Boston campus in 1998, wanted to bring MIT's expertise to the UK. A BankBoston report of 1997 found that MIT-related companies employed 1.1m people with annual worldwide sales of $232bn (£160bn). Companies founded by MIT graduates include Hewlett-Packard, Rockwell International, McDonnell Douglas, Intel and Campbell's Soup. Fundamental institutional differences show themselves at the student level, too. Currently, 33 students from Cambridge are at MIT and 27 from MIT at Cambridge. "Another example of cultural differences is our contrasting attitudes towards the independence and maturity of our students," says Mr [John Vander Sande]. "We check that they are keeping up with the subject on a weekly, if not a daily, basis," he says - an example of a "fair amount of hand-holding". Prof [Alan Windle] says the Cambridge tutorial system underpins the university's quality but there have been changes, such as more course work. "Each system is very good. We are not trying to make Cambridge like MIT and they're not trying to make MIT like Cambridge." There is cross-fertilisation. MIT students do broad-based degrees in which scientists spend 25 per cent of their time on HAS courses: humanities, arts and social science. MIT students have complained that Cambridge's courses are too highly specialised. "We do 100 per cent physics after the third year. That's because we want to turn out the best physicists in the world," says Prof Windle. But Cambridge is designing HAS modules for students as a result of the MIT experience.